MAGNESIUM DEFICIT AS A MODERN NUTRITIONAL ISSUE IN CHILDREN AND ADOLESCENTS - O. Alekseevna Gromova (Педиатрическая фармакология, 2014)
The review is dedicated to the issues of body magnesium deficit. The authors used data of the evidence-based trials. The authors consider pathologic conditions predisposed by magnesium deficit, i.e. excess weight and obesity, attention deficit and hyperactivity disorder, impaired glucose intolerance, arterial hypertension, gallstone disease and other conditions in detail. The authors dwell upon ways of magnesium deficit correction. The article shows that the most effective method is application of organic magnesium salts (lactate, pidolate, citrate).